The combination of fatigue with the serum GCSF improves the performance of serological screening for frailty - Yu Jiaming; Chen Jie; Ji Xueying; Qiu Yixuan; Zhang Yan; Wang Jiaofeng; Li Xiangqi; Zhang Chaobao; Bao Zhijun (Acta Biochimica et Biophysica Sinica)
Frailty is a critical cause leading to elderly death. No drug is available to treat it, while prevention works. However, reliable blood screening and diagnostic methods for frailty are still lacking. Here, we show that the serum GCSF, in combination with the fatigue factor of the frailty scale, can improve the performance of serological screening for frailty. • Proteomics studies indicate that frailty and aging exhibit distinct inflammatory niches. • Among 15 serum inflammatory markers, IFNγ, GCSF, and TNFα are significantly reduced in frail patients. • The combination of serum GCSF level and fatigue factor among the frailty scale can be used for frailty screening.